Effect of population density of Chenopodium album on wheat (Triticum aestivum) - KARIM, S M REZAUL; MAMUN, A A; MAKHAL, P K (The Indian Journal of Agricultural Sciences, 2013)
A study was conducted during 1992-93 on weed density effect of Chenopodium album on wheat (Triticum aestivum L. emend.Fiori & Paol.) in pots at Mymensingh, Bangladesh. Three densities of the weed (56, 112 and 224/m2) were established in each of the 3 crop densities (56, 112 and 224/m2). Results showed that dry matter ofwheatlplant, grain yields/plant and weed dry matter/plant were reduced progressively with the increase in both weed and crop densities. However, significantly higher grain yield/pot was observed due to increase in crop density. No effect of weed density on grain yield/pot was noted. The effect of crop and weed density on number of tillers/plant, number of panicle/plant and number of grains/panicle were similar to that of grain yield/plant. The interaction eftect of crop and weed density was significant only in weed dry matter/plant when monoculture of weed was included. The crop tolerated the detrimental effects of C. album'up to weed density of 224/m2 without much loss in its yield The competitive ability of the weed as measured by aggressivity was significantly higher at low density of weed but it was unaffected under different crop densities.